Physical activity interventions in European primary schools: a scoping review to create a framework for the design of tailored interventions in European countries - Alice Porter; Alice Porter; Robert Walker; Danielle House; Ruth Salway; Sarah Dawson; Sarah Dawson; Sharea Ijaz; Sharea Ijaz; Frank de Vocht; Frank de Vocht; Russell Jago; et al. (Frontiers Media S.A., 2024)
IntroductionSchools provide a unique environment to facilitate physical activity for children. However, many school-based physical activity interventions have not been effective. We propose a new approach, which allows schools to tailor interventions to their specific context. This scoping review aimed to identify intervention components from previous school-based physical activity interventions to form the basis of a tailored approach in a European setting.MethodsJoanna Briggs Institute guidelines for conducting scoping reviews were followed. European school-based intervention studies aimed at increasing physical activity in children aged 7-11 years published in English since 2015 were included. Databases searched were Ovid Medline, Embase, PsycINFO, Web of Science Social Sciences Citation Index, ERIC and British Education Index. Data was extracted on intervention components, context-related factors (geographical location, school size, child socioeconomic status and ethnicity), feasibility, acceptability and cost-effectiveness. A data-driven framework was developed to summarize the identified intervention components.Results79 articles were included, constituting 45 intervention studies. We identified 177 intervention components, which were synthesized into a framework of 60 intervention component types across 11 activity opportunities: six within the school day, three within the extended school day and two within the wider school environment. Interventions most frequently targeted physical education (21%), active and outdoor learning (16%), active breaks (15%), and school-level environmewnt (12%). Of the intervention components, 41% were delivered by school staff, 31% by the research team, and 24% by external organizations. Only 19% of intervention studies reported geographical location and only 10% reported school size. Participant ethnicity and socioeconomic information was reported by 15% and 25%, respectively. Intervention acceptability was reported in 51% of studies, feasibility in 49%, and cost effectiveness in 2%.DiscussionThis review offers a first step in developing a future framework to help schools to develop context-specific, tailored interventions. However, there was a lack of reporting of contextual factors within the included studies, making it difficult to understand the role of context. Future research should seek to measure and report contextual factors, and to better understand the important aspects of context within school-based physical activity.